2022
DOI: 10.1002/ps.6820
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of enhanced reproductive performance and lack‐of‐fitness costs among soybean aphids, Aphis glycines, with varying levels of pyrethroid resistance

Abstract: BACKGROUND Foliar application of insecticides is the main strategy to manage soybean aphid, Aphis glycines (Hemiptera: Aphididae), in the northcentral United States. Subpopulations of A. glycines have multiple nonsynonymous mutations in the voltage‐gated sodium channel (vgsc) genes that are associated with pyrethroid resistance. We explored if fitness costs are associated with phenotypes conferred by vgsc mutations using life table analyses. We predicted that there would be significant differences between pyre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…It is known that the changes of biological parameters in insects is caused by genetic alteration and the fitness change with its resistance level to insecticides. For example, Valmorbida et al found that A. glycines carrying the heterozygous super-kdr M918I+L1014F genotype had significant reproductive advantages [ 51 ]. The relative fitness of pyrethroid-resistant and organophosphate-resistant Sitophilus zeamais varied in different geographical populations [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the changes of biological parameters in insects is caused by genetic alteration and the fitness change with its resistance level to insecticides. For example, Valmorbida et al found that A. glycines carrying the heterozygous super-kdr M918I+L1014F genotype had significant reproductive advantages [ 51 ]. The relative fitness of pyrethroid-resistant and organophosphate-resistant Sitophilus zeamais varied in different geographical populations [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acetamiprid-selected strain exhibited a higher reproductive rate, intrinsic rate, biotic potential than those of the laboratory susceptible and unselected field strains. Recently, Valmorbida et al 47 reported that pyrethroid resistant Aphis glycine Matsumura represented enhanced reproductive performance and lack of fitness costs of biological events.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, deltamethrin (a pyrethroid) resistance resulted in a significant fitness cost in a strain of Aedes albopictus (Skuse) from China 49 , but exposure to the same insecticide resulted in enhanced fitness in a strain of Sitophilus zeamais (Motschulsky) from Brazil 50 . Bifenthrin, another pyrethroid, caused fitness cost in Rhopalosiphum padi (L.) 51 ; however, Valmorbida et al 47 reported lack of fitness cost in A. glycine following exposure to bifenthrin. Similarly, exposure to Bacillus thuringiensis -based toxins resulted in a significant fitness cost in a strain of Plutella xylostella (L.) from Malaysia 52 , but exposure to the same toxin resulted in lack of fitness costs in another strain of P. xylostella from Florida 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Lack of fitness costs and higher fecundity and fertility were reported in insecticide-resistant Western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), from southeastern Spain (Bielza et al 2008) and soybean aphids, Aphis glycines Matsumura (Hemiptera: Aphididae), from the USA (Menger et al 2022, Valmorbida et al 2022). Colorado potato beetles selected for feeding on a resistant wild potato host ( Solanaceum berthaultii ) also produced significantly more eggs compared to beetles fed on common potato ( S. tuberosum ) (Groden and Casagrande 1996).…”
Section: Discussionmentioning
confidence: 99%